MURABAHAH IN ISLAMIC BANKING SYSTEM - Fariz Al-Hasni (Universitas Islam Negeri Mataram, 2019)
Islamic bank products have similarities but are not the same as conventional bank products because they have a ban on usury, gharar, and maysir. Therefore, approval and financing products such as working capital and investment in the form of sale and purchase agreements in Islamic banks must be avoided. sale and purchase agreement that has been discussed by Islamic scholars of muamalah is very much Islamic. The amount can reach dozens if not reached. Even so, of these many forms, there are three types of buying and selling that have been developed as the main support in working capital and investment financing in Islamic banking, namely, bai'al-murabahah, bai 'as-salam, and bai' al-istishna '.